Armenians of Russia: geo-demographic trends of the past, modern realities and prospects - Sergeiy Sushchiy (Демографическое обозрение, 2019)
The article analyzes the quantitative growth, spatial dynamics, gender structure and form of resettlement of the Armenian population of Russia in the 18th-20th centuries. The demographic correlation of the largest regional communities at different stages of their development are studied, and the main historical periods of the geo-demographic dynamics of the Armenians of Russia are determined.